2020
DOI: 10.5751/ace-01565-150116
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in crane migration phenology associated with climate change in southwestern Europe

Abstract: Gallocanta lagoon, NE Spain, is one of the main stopover and wintering areas of Common Cranes (Grus grus) migrating through Western Europe. We investigated how the water level of the lagoon where cranes roost, precipitation, and air temperature might have influenced the species' migration and wintering patterns in this area between 1973 and 2018. Over the study period, the mean annual air temperature increased at 0.3 °C per decade. Simultaneously, cranes advanced the spring peak migration date at a rate of 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Mean annual and seasonal temperature can influence the migratory, foraging behavior, and site selection of a species [142][143][144]. Our results indicated that temperature seasonality and annual mean temperature play major roles in defining Demoiselle Crane habitat suitability.…”
Section: Discussionmentioning
confidence: 89%
“…Mean annual and seasonal temperature can influence the migratory, foraging behavior, and site selection of a species [142][143][144]. Our results indicated that temperature seasonality and annual mean temperature play major roles in defining Demoiselle Crane habitat suitability.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, decreasing rainfall and increasing temperatures may also have an impact through changes in the environmental conditions of resting sites. For this reason, for example, one of the most important stopover sites in Spain had an earlier peak in spring migration of 0.37 days per year between 1973and 2018(Orellana Macías et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Gallocanta Lake is surrounded by vegetation and the lake bed is colonized by Ruppia drepanensis, which is a rooted submerged macrophyte commonly found in ephemeral saline inland wetlands of the Mediterranean region [31][32][33] . Also, it harbours a large community of migratory crane (Grus grus) from November to March each year [34][35][36] . Therefore, birds excrements and vegetation decay (mainly R. drepanensis) represent a significant source of organic matter and nutrients to the lake.…”
Section: Organic Matter Inputsmentioning
confidence: 99%